DISCOURSE ANALYSIS THE USE OF FORMAL AND INFORMAL LANGUAGE IN SOCIAL MEDIA - Murni Mahmud; Muftihaturrahmah Burhamzah; Mutiara Mutiara (State University of Makassar, 2026)
This study explores the use of formal and informal language in social media, specifically examining Instagram posts by Arini Nurwijayanti, an influencer based in Makassar, Indonesia. The research employs a qualitative approach, utilizing discourse analysis to understand the linguistic features present in her social media interactions. Data was collected from Arini Nurwijayanti's Instagram account (@arininurwijayanti), focusing on textual data from her posts. The collected data was then analyzed using a discourse analysis framework, examining syntax and sentence structure, the use of abbreviations, slang, emojis, and hashtags, as well as the degree of grammatical correctness. The findings reveal a dominant use of informal language in Arini's posts, characterized by simple sentence structures, colloquial vocabulary (e.g.,